Metallic nanocarrier complex targeting neuroendocrine prostate cancel cells. - Hemben, Aver (Cranfield University, 2022)
Iron oxide nanoparticles were successfully produced by inert gas condensation using the Mantis NanoGen Trio system. The nanoparticles were produced via a novel approach using the Physical Vapour Deposition (PVD) method to condense iron oxide nanoparticles of small size and small size distribution of 1-6 nm diameter. The sputtered nanoparticles were soft-landed on a polyethylene glycol-coated silicon wafer, then dispersed in RNAse free water (PEG-IONPs) to functionalise them for biocompatibility and use in nanocarrier synthesis. The sputtered iron oxide nanoparticles were characterised by transmission electron microscopy, atomic force microscopy, nanoparticle tracking analysis, dynamic light scattering and magnetic resonance imaging. The different techniques demonstrated that whereas the IONPs themselves were less than 10 nm (seen by TEM) the PEG-IONPs demonstrated a size range slightly different according to the technique used for its evaluation (e.g.47 ± 22.75 nm by DLS and 143 ± 100 nm by NTA) with the variation most likely due to the high concentration of PEG present in solution. In parallel to sputtering IONPs, commercial iron oxide nanoparticles (CIONPs) were used to demonstrate and optimise the attachment of a therapeutic drug (siRNA) to the nanoparticles in 1:1 polyethylene glycol and polyethyleneimine. Then the release profile of the attached siRNA from CIONPs in PBS buffer pH 6.4 and 7.4 was studied. While using a sample of PBS/PEG/PEI, approximately 75% of siRNA was attached to CIONPs and approximately 86% siRNA was released in PBS after 300 minutes of incubation at 37°C. The research findings demonstrate the potential use of the synthesised nanoparticles and nanocarrier complex in targeted drug deliver to neuroendocrine prostate cells.
Keywords: Iron oxide nanoparticles; inert gas condensation sputtering; drug delivery; prostate cancer metallic nanoparticles; metallic nanocarrier; Physical Vapour Deposition (PVD)